Witness testimonial credibility in criminal proceedings - Ayala Yancce, Rafael (2020)
Nowadays, the great majority of the judges to assess the credibility of the testimonies within the criminal process as a first point analyze the personal characteristics and physiological changes of the witness, leaving aside the functionality of human memory. The psychology of the testimony tells us that in order to assess credibility, it is not necessary to examine the characteristics of the witness, but rather that the correspondence between what happened and what the witness manifests from what he has perceived must be analyzed, since this allows us to differentiate between the experiences lived from those imagined or invented stories. The objective of this article is to analyze the accuracy of the memory when reproducing the information. Once the accuracy of the report and the failures in the recovery of the information have been analyzed, I will focus on presenting the steps or criteria for assessing the testimonial credibility of the eyewitnesses and referential witnesses that the judge must take into account when motivating the judgment.